UJI PELAPUKAN LIMA JENIS KAYU YANG DIPASANG SEKRUP LOGAM - Sihati Suprapti; Djarwanto (Jurnal Penelitian Hasil Hutan, 2015)
This study examining study fungal resistance properties of five wood species using Kolle-flask method. The studied wood species include: ki hiur (Castanopsis acuminatissima), huru pedes (Cinnamomum iners), huru koja (Litsea angulata), ki kanteh (Ficus nervosa), and kelapa ciung (Horsfieldia glabra). Samples were grouped into inner part and outer part of logs as well as metal screwed and unscrewed. Results show that all of five studied wood species no matter parts of log are classified not-resistant (class IV). Weight loss of wood samples with the attached metal screw is higher in average than the unscrewed wood samples. The highest weight loss was recorded on the inner part of unscrewed huru pedes wood exposed to Pycnoporus sanguineus. While the lowest weight loss was found in screwed samples of the same species exposed to Dacryopinax spathularia. The metal screws were found corroded after the test and the highest screw weight loss was found on ki kanteh wood. Metal screw that attached on the inner part experienced lower eight lost than screws attached on the outer part of log.